ChatGPT’s Impact on Students’ Writing: Lessons Learned from Nepali Undergraduate Students - Sherma, Amar Bahadur (Journal of NELTA, 2024)
Artificial Intelligence (AI) has significantly evolved and is widely applied across various sectors, including education. The advent of ChatGPT has generated interest among users and researchers. Some express concerns about student dependency, while others advocate its incorporation into education due to its growing indispensability. ChatGPT offers a platform for students to address difficult theoretical questions and generate ideas for application-based questions. A study was conducted to understand undergraduate students’ perceptions of Chat GPT’s usefulness in academic writing and explore its potential in Nepali education. Using a mixed-method approach, data was gathered through a structured questionnaire distributed online via Messenger and email. The respondents, 64 Nepali students pursuing undergraduate degrees in Nepal and abroad, answered six questions: 5 questions were structured, and 1 question was unstructured. The study revealed that most students found ChatGPT easy to use and beneficial for idea generation, rephrasing, and correcting grammatical errors. However, concerns about dependency and its impact on creativity were noted. While ChatGPT is a valuable tool for enhancing writing skills, a balanced approach is necessary to leverage AI’s capabilities while fostering independent thinking. Further research is recommended to explore long-term impacts and effective integration strategies in education.